1975
DOI: 10.1115/1.3450295
|View full text |Cite
|
Sign up to set email alerts
|

Laser Interferometric Investigation of the Microlayer Evaporation Phenomenon

Abstract: An experimental investigation is presented in which the growth and evaporation of the microlayer underlying a bubble forming on a glass heater surface has been studied using laser interferometry and high speed photography. The results presented for a single bubble indicate that the microlayer thickness is of the order of 5 μm. Subsequent analysis of these results confirms that the microlayer evaporation phenomenon is a significant heat transfer mechanism, representing approximately 25 percent of the total nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 0 publications
2
33
0
Order By: Relevance
“…50 The existence of this thin liquid film, called the micro-layer, was confirmed experimentally using optical interferometry by Sharp [27] and Jawurek [28] in the 1960's. These pioneering works were followed by several others [29][30][31], all with similar conclusions. These works revealed that the thickness of the micro-layer is of the order of few micrometers.…”
Section: Introductionmentioning
confidence: 55%
“…50 The existence of this thin liquid film, called the micro-layer, was confirmed experimentally using optical interferometry by Sharp [27] and Jawurek [28] in the 1960's. These pioneering works were followed by several others [29][30][31], all with similar conclusions. These works revealed that the thickness of the micro-layer is of the order of few micrometers.…”
Section: Introductionmentioning
confidence: 55%
“…Judd and Hwang [12] used Voutsinos and Judd [20] experimental results (on dichloromethane) for the initial microlayer thickness (1-6 lm depending on the surface heat flux) to calculate the total microlayer volume. Also, they determined the nucleation site density (n = N/A T ) experimentally.…”
Section: Judd and Hwang [12] Modelmentioning
confidence: 99%
“…Jawurek [5] measured the microlayer thickness to be 0.5 lm for ethanol on a glass surface by using a similar method. Furthermore, by using a laser light source, Voutsinos and Judd [6] measured the microlayer thickness in dichloromethane to be in the range 1-6 lm. They found that the thickness increased with increasing distance from the incipient bubble site.…”
Section: Introductionmentioning
confidence: 99%